2010
DOI: 10.1021/jp910778j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Thermochemical Study and Solid-Phase Structure of 5,5-Dimethylbarbituric Acid

Abstract: This paper reports an experimental and computational thermochemical study on 5,5-dimethylbarbituric acid and the solid-phase structure of the compound. The value of the standard (p(o) = 0.1 MPa) molar enthalpy of formation in the gas phase at T = 298.15 K has been determined. The energy of combustion was measured by static bomb combustion calorimetry, and from the result obtained, the standard molar enthalpy of formation in the crystalline state at T = 298.15 K was calculated as -(706.4 +/- 2.2) kJ x mol(-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
4
15
0
Order By: Relevance
“…The MP2/6-31G(d,p) optimized molecular structure of 5,5-dimethylbarbituric acid is also a C5-endo envelope conformation, as observed in the experimental crystal structure, and is in agreement with previous calculations performed at the MP2/6-31G(d) level of theory [30]. However, using a DFT (PBE0) method with different basis sets, a nearly planar pyrimidine ring and ∆d values of less than 0.01 Å were obtained.…”
Section: Compound (X X 1 ) Level Of Theory Ring Conformationsupporting
confidence: 90%
See 1 more Smart Citation
“…The MP2/6-31G(d,p) optimized molecular structure of 5,5-dimethylbarbituric acid is also a C5-endo envelope conformation, as observed in the experimental crystal structure, and is in agreement with previous calculations performed at the MP2/6-31G(d) level of theory [30]. However, using a DFT (PBE0) method with different basis sets, a nearly planar pyrimidine ring and ∆d values of less than 0.01 Å were obtained.…”
Section: Compound (X X 1 ) Level Of Theory Ring Conformationsupporting
confidence: 90%
“…However, using a DFT (PBE0) method with different basis sets, a nearly planar pyrimidine ring and ∆d values of less than 0.01 Å were obtained. In a previous report, Roux and coworkers have shown that the planar conformation becomes more stable than the C5-endo envelope if another DFT method, B3LYP, and a different basis set or the combination MP2/6-31(3df,2p) are used [30]. The disagreement between the methods indicates that the steric effect of the Me group on the ring conformation is less pronounced than that of a halogen substituent.…”
Section: Compound (X X 1 ) Level Of Theory Ring Conformationmentioning
confidence: 99%
“…In the context of a systematic study of the thermodynamic properties of this family of compounds and despite the important uses and applications of barbituric acid derivatives, reliable experimental thermochemical studies in literature are scarce . We have recently published thermochemical studies of the parent compound barbituric acid and its 5,5-dimethyl, 1,3-dimethyl, and 5,5-diethyl (barbital) derivatives. , We have also reported thermophysical studies of 2-thiobarbituric acid and some methyl and ethyl derivatives of barbituric acid …”
Section: Introductionmentioning
confidence: 99%
“…In the context of a systematic study of the thermodynamic properties of this family of compounds and despite the important uses and applications of barbituric acids derivatives, reliable experimental thermochemical studies in the literature are scarce. We have recently published thermochemical studies of the parent compound barbituric acid and its 5,5-dimethyl and 5,5-diethyl (barbital) , derivatives.…”
Section: Introductionmentioning
confidence: 99%